2021
DOI: 10.1038/s41598-021-01566-y
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory patterns for continuous metabolic syndrome score in childhood and the cardiovascular risk in adolescence

Abstract: We explored the association between the trajectory of the continuous metabolic syndrome score (cMetS) in childhood with high-sensitivity C-reactive protein (hs-CRP) and carotid intima-media thickness (CIMT), which are known to increase cardiovascular disease risk in adolescence. The trajectory of cMetS in childhood (from 3 to 12 years of age) was identified in 833 children who participated in the Ewha Birth and Growth Study. The associations between cMetS and hs-CRP and CIMT were analyzed in 204 out of 833 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…How MetS is determined in children and adolescents overlooks developmental differences based on age and sex, and the IDF definition states that MetS cannot be diagnosed in children under 10 years of age [27]. One cohort study tracked individual cMetS from age 3 through adolescence and found a stable pattern [28]. Studies conducted in Chile and Spain have also assessed MetS risk using cMetS in children under 10 years of age [16,17].…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…How MetS is determined in children and adolescents overlooks developmental differences based on age and sex, and the IDF definition states that MetS cannot be diagnosed in children under 10 years of age [27]. One cohort study tracked individual cMetS from age 3 through adolescence and found a stable pattern [28]. Studies conducted in Chile and Spain have also assessed MetS risk using cMetS in children under 10 years of age [16,17].…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…41) The cMetS remained stable throughout childhood. 42) NAFLD is often asymptomatic and can lead to irreversible complications, highlighting the importance of early diagnosis to prevent progression. The global prevalence of NAFLD is 4.2%-9.6% and can reach 38% in pediatric obese populations.…”
Section: Studies Using Metabolic Complication Assessment Indicatorsmentioning
confidence: 99%
“…Additionally, in the International Childhood Cardiovascular Cohort Consortium (average follow-up, 22.3 years), cMetS in childhood was associated with a 2.1-fold higher risk of MetS in adulthood [ 41 ]. The cMetS remained stable throughout childhood [ 42 ]. NAFLD is often asymptomatic and can lead to irreversible complications, highlighting the importance of early diagnosis to prevent progression.…”
Section: Metabolic Complications Associated With Pediatric Obesitymentioning
confidence: 99%